Peran Pertanian Organik Berbasis Ternak dalam Mendukung Ketersediaan Pangan Sehat dan Aman dn Mencapai Kelestarian Pertanian-Lingkungan - Didik Wisnu Widjajanto; T. Honmura (Caraka Tani: Journal of Sustainable Agriculture, 2005)
Practicing intensive agriculture by implementing chemical substances in agriculture systems have been suspected cause problem on environment. Increase content of nitrate in drinking water and aquatic systems and greenhouse gases status of atmosphere may be due to the miss-practice of agricultural activity. Organic farming (OF) is one of techniques that may be implemented in order to solve this problem. Besides, its benefit in maintaining agro-environmental sustainability, practicing OF has weakness in the field. Therefore, to achieve its goal suitable strategy is needed. In the OF based on livestock, integration of crop-livestock-soil may occur, where among those three interact one each other and therefore ideal system (Zero wastes) may be established. Improvement of pasture increase, highly forage crop productivity and availability is expected influence on the performance of livestock. On the other hand, the return of animal wastes into pasture may tend to decrase the risk of environmental pollution.